2018
DOI: 10.1088/1367-2630/aaca23
|View full text |Cite
|
Sign up to set email alerts
|

The radial acceleration relation and a magnetostatic analogy in quasilinear MOND

Abstract: Recently a remarkable relation has been demonstrated between the observed radial acceleration in disk galaxies and the acceleration predicted on the basis of baryonic matter alone. Here we study this relation within the framework of the modified gravity model MOND. The field equations of MOND automatically imply the radial acceleration relation (RAR) for spherically symmetric galaxies, but for disk galaxies deviations from the relation are expected. Here we investigate whether these deviations are of sufficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Instead, it requires the weaker condition that departures of g from spherical symmetry are accurately captured by applying the MOND ν function to g N , which is itself not spherically symmetric. This may explain why Jones-Smith et al (2018) found that QUMOND gravitational fields in disk galaxies could be estimated rather well using the algebraic MOND approximation, justifying our use of Equation 7. We discuss its accuracy in Section 9.3.1, finding it should work well in the Solar neighbourhood where the WBT would be conducted.…”
Section: Governing Equationssupporting
confidence: 55%
See 1 more Smart Citation
“…Instead, it requires the weaker condition that departures of g from spherical symmetry are accurately captured by applying the MOND ν function to g N , which is itself not spherically symmetric. This may explain why Jones-Smith et al (2018) found that QUMOND gravitational fields in disk galaxies could be estimated rather well using the algebraic MOND approximation, justifying our use of Equation 7. We discuss its accuracy in Section 9.3.1, finding it should work well in the Solar neighbourhood where the WBT would be conducted.…”
Section: Governing Equationssupporting
confidence: 55%
“…This is known to work rather well in disk galaxies, at least once the vertical Newtonian gravity g N,z is taken into account when determining ν so as to more rigorously implement the algebraic MOND approximation (Jones-Smith et al 2018). For a thin disk, g N,z may be estimated as g N,z = − 2πGΣ sign (z)…”
Section: The Effect Of the Galactic Diskmentioning
confidence: 99%
“…This approximation is exactly correct in spherical symmetry and works rather well in axisymmetric problems (Angus et al 2012;Jones-Smith et al 2018). It is expected to work particularly well just outside the disc ).…”
Section: Initializing a Milgromian Discmentioning
confidence: 76%
“…As a general comment, we note that it is impractical, in general, to solve a many-body system in full, but as is usually realized, there are problems where we can apply a mean-field approximation, where we consider the motion of a single body (e.g., a star in a galaxy) in the combined mean field of all the others assumed time independent. 9 In some important applications, the motion of the constituents is described, to a good approximation, as the combination of several trajectories, with distinct frequencies, or of bunches of frequencies (which we lump into one for simplicity),…”
Section: Examplesmentioning
confidence: 99%
“…Among second-tier predictions, one may count some fine details of the rotation curves (e.g., Refs. [8][9][10][11]), the exact value of η in the M − σ relation, and its dependence on dimensionless attributes of the system; the exact dependence of the effective two-body force on the masses; the exact nature and strength of the external-field effect, etc.…”
Section: Introductionmentioning
confidence: 99%